The Influence of Different EEG References on Scalp EEG Functional Network Analysis During Hand Movement Tasks - Zhang, Lipeng; Wang, Peng; Zhang, Rui; Chen, Mingming; Shi, Li; Gao, Jinfeng; Hu, Yuxia (Frontiers in Human Neuroscience, 2020)
Although functional networks have been applied to the study of motor tasks using electroencephalography, the selection of a suitable reference electrode has not been sufficiently researched. In order to investigate the effects of the original reference (REF), the common average reference (CAR), and the reference electrode standardization technique (REST) on brain functional network analysis during hand movement tasks, electroencephalograms (EEGs) of 10 right-handed subjects performing self-paced hand movements were collected, and functional networks (coherence (COH), phase-locking value (PLV), phase lag index (PLI)) with different references were constructed. Compared with the REF reference, the networks with CAR and REST references exhibited more significant increases in connectivity during the left-/right-hand movement preparation and movement execution stages. The node degree of the channel near the reference electrode was significantly reduced by the REF reference. CAR and REST both decreased this reference effect, REST more so than CAR. We confirmed that the choice of reference would affect the analysis of the functional network during hand movement tasks, and the REST reference can greatly reduce the effects of the physical reference on the analysis of EEG connectivity.